Latin American Consensus on the Management of Sepsis in Children: Sociedad Latinoamericana de Cuidados Intensivos Pediátricos [Latin American Pediatric Intensive Care Society] (SLACIP) Task Force: Executive Summary. (June 2022) - Fernández-Sarmiento, Jaime; De Souza, Daniela Carla; Martinez, Anacaona; Nieto, Victor; López-Herce, Jesús; Soares Lanziotti, Vanessa; Arias López, María del Pilar; De Carvalho, Werther Brunow; Oliveira, Claudio F.; Jaramillo-Bustamante, Juan Camilo; Díaz, Franco; Yock-Corrales, Adriana; et al.
Objective: The aim of this study was to develop evidence-based recommendations for the diagnosis and treatment of sepsis in children in low- and middle-income countries (LMICs), more specifically in Latin America.Design: A panel was formed consisting of 27 experts with experience in the treatment of pediatric sepsis and two methodologists working in Latin American countries. The experts were organized into 10 nominal groups, each coordinated by a member.Methods: A formal consensus was formed based on the modified Delphi method, combining the opinions of nominal groups of experts with the interpretation of available scientific evidence, in a systematic process of consolidating a body of recommendations. The systematic search was performed by a specialized librarian and included specific algorithms for the Cochrane Specialized Register, PubMed, Lilacs, and Scopus, as well as for OpenGrey databases for grey literature. The GRADEpro GDT guide was used to classify each of the selected articles. Special emphasis was placed on search engines that included original research conducted in LMICs. Studies in English, Spanish, and Portuguese were covered. Through virtual meetings held between February 2020 and February 2021, the entire group of experts reviewed the recommendations and suggestions.Result: At the end of the 12 months of work, the consensus provided 62 recommendations for the diagnosis and treatment of pediatric sepsis in LMICs. Overall, 60 were strong recommendations, although 56 of these had a low level of evidence.Conclusions: These are the first consensus recommendations for the diagnosis and management of pediatric sepsis focused on LMICs, more specifically in Latin American countries. The consensus shows that, in these regions, where the burden of pediatric sepsis is greater than in high-income countries, there is little high-level evidence. Despite the limitations, this consensus is an important step forward for the diagnosis and treatment of pediatric sepsis in Latin America.